Development of animal feed based on cocoa shell waste in the Tomata Ndeme Farmer Group - Andri Amaliel Managanta; Yan Alpius Loliwu; Ika Paramitha Lantu (Community Empowerment, 2024)
Cocoa is an important agricultural commodity for the economy of farmers in Central Sulawesi, especially in Poso Regency. However, cocoa farming faces challenges such as low farmer competence and less-than-optimal management, particularly in its integration with livestock. Therefore, the development of environmentally friendly agricultural techniques is needed to increase cocoa production and enhance food security. The purpose of implementing the Community Partnership Empowerment (PKM) program was to improve farmers' knowledge, skills, and attitudes regarding the processing of cocoa pod waste into animal feed. This participatory program focused on developing farmer resources by utilizing local potential within the Tomata Ndeme Farmer Group in Sepe Village, Lage District, Poso Regency. Results showed a significant increase in farmers' management abilities, with knowledge scores rising from 63.5 to 80.3, attitudes from 53.3 to 70.4, and skills from 24.1 to 67.6. The previously worthless cocoa pod waste is now being used as cattle feed.